The Anti-Inflammatory and Free Radical Scavenging Activities of Bio-Inspired Nano Magnesium Oxide - Shahid, Sammia; Ejaz, Anam; Javed, Mohsin; Mansoor, Sana; Iqbal, Shahid; Elkaeed, Eslam B.; Alzhrani, Rami M.; Alsaab, Hashem O.; Awwad, Nasser S.; Ibrahium, Hala A.; Fatima, Urooj; Zaman, Sabah; et al. (Frontiers in Materials, 2022)
This work includes green synthesis of magnesium oxide nanoparticles (MgO NPs) by using Alstoniascholaris, which is indigenous to many countries such as China, Australia, Sri Lanka, Pakistan, and India. Its pharmacological activities include antidiabetic, antioxidant, anticancer, analgesic, antitussive, and anti-diarrheal activities. In this study, the antioxidant and anti-inflammatory activities of bio-inspired magnesium oxide nanoparticles, MgO NPs, were investigated. MgO NPs were prepared by using the leaf extract of Alstonia scholaris, followed by characterization using EDX, XRD, and SEM techniques. The crystallite size of magnesium oxide nanoparticles was 19.57 nm. XRD analysis confirmed the crystallinity and the purity of MgO NPs. Anti-inflammatory activity was carried out to observe inhibition of protein denaturation. Since the IC50 of MgO nanoparticles was lower than the standard, it was found to be more effective. IC50 values were compared, and results reveal that bioinspired MgO NPs undergo more scavenging of free radicals than standard (ascorbic acid) MgO NPs. These MgO nanoparticles are useful in cosmetics such as scrubs, moisturizers, and an active ingredient in microdermabrasion and in formulating effective drugs for maintaining the protein structure of the body, which will reduce inflammation.